Deep Eutectic Solvents for the Removal of Lead Contaminants in Mangrove Soil - Shahidah Nusailah Rashid; Hanee F. Hizaddin; Adeeb Hayyan; Khairunnisa Hasikin; Sarah Abdul Razak; Mohd Istajib Mokhtar; Muhammad Mokhzaini Azizan (Sciencedirect, 2024)
Indexed by WOS/Scopus/ERA